1982
DOI: 10.1113/jphysiol.1982.sp014063
|View full text |Cite
|
Sign up to set email alerts
|

Calcium and potassium currents in muscle fibres of an insect (Carausius morosus).

Abstract: SUMMARY1. A three electrode voltage-clamp was used to investigate membrane currents in the skeletal muscle fibres of the stick insect, Carausius morosus. Contraction was blocked by hypertonic solutions.2. Membrane currents elicited by step depolarizations consisted of an inward current, an early outward current and a delayed outward current.3. The reversal potential of the delayed outward current did not change when S042-was substituted for Cl-, but shifted by 14-1 mV when [K]o was increased from 20 mM to 40 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
44
1

Year Published

1985
1985
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(55 citation statements)
references
References 74 publications
(122 reference statements)
10
44
1
Order By: Relevance
“…Analysis of Drosophila larval muscles has revealed several physiologically distinct membrane currents similar to those found in other insect muscles (Yamamoto and Washio, 1981;Yamamoto et al, 1981;Ashcroft and Stanfield, 1982). Voltage-dependent Ca2+ channels are responsible for the inward current but Na+ channels are not detectable in the larval muscles, consistent with a previous current clamp study (Suzuki and Kano, 1977).…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…Analysis of Drosophila larval muscles has revealed several physiologically distinct membrane currents similar to those found in other insect muscles (Yamamoto and Washio, 1981;Yamamoto et al, 1981;Ashcroft and Stanfield, 1982). Voltage-dependent Ca2+ channels are responsible for the inward current but Na+ channels are not detectable in the larval muscles, consistent with a previous current clamp study (Suzuki and Kano, 1977).…”
Section: Discussionsupporting
confidence: 77%
“…In Drosophila larval muscles, IK inactivates slowly, resembling the observations reported in a number of different tissues including frog skeletal muscles (Adrian et al, 1970) and adult stick insect muscles (Ashcroft and Stanfield, 1982). Depletion of intracellular K+ or accumulation of external K+ in the vicinity of the membrane surface may also lead to decline of /k.…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…However, a two-time-constant recovery from inactivation was not strongly supported because (1) the correlation coefficient for the fast phase (-0-81) is lower and (2) the related time constant (0-24 s) is very close to the test-pulse duration. These results can be compared with those obtained for Ca2+ current by other authors who concluded that two time constants existed using a similar two-pulse protocol: 0 42/4A4 s (Tillotson & Horn, 1978); _0,1/ _1 s (Adams & Gage, 1979); 0 12/9 4 s (Plant & Standen, 1981); 0-06/0 89 s (Ashcroft & Stanfield, 1982).…”
Section: Recovery From Inactivationmentioning
confidence: 74%
“…Inactivation of Ca2+ entry It has been suggested in a number of preparations (Hagiwara & Nakajima, 1966;Tillotson, 1979;Ashcroft & Stanfield, 1982;Standen & Stanfield, 1982;Eckert & Ewald, 1983) that the intracellular free Ca2+ controls the inactivation of the Ca2+ channel. However, in most experiments the precise evaluation of Ca2+ current is difficult since it is usually contaminated by the outward current which is very difficult to eliminate.…”
Section: Characteristics Of Ca2+ Entrymentioning
confidence: 99%